Work–Life Balance: History, Costs, and Budgeting for Balance - Raja, Siva; Stein, Sharon L. (Clinics in Colon and Rectal Surgery, 2014)
The concept and difficulties of work–life balance are not unique to surgeons, but professional responsibilities make maintaining a work–life balance difficult. Consequences of being exclusively career focused include burn out, physical, and mental ailments. In addition, physician burn out may hinder optimal patient care and incur significant costs on health care in general. Assessing current uses of time, allocating goals catered to an individual surgeon, and continual self-assessment may help balance time, and ideally will help prevent burn out.
Keywords: work–life balance; physician burn out; creation of goals